Gas-particle partitioning of carbonyl compounds in the ambient atmosphere - H.Q. Shen; Chen, Z. M.; H. Li; X. Qian; X. Qin; W.X. Shi (Environmental Science & Technology, 2018)
Despite their crucial roles in health and climate concerns, the gas-particle partitioning of carbonyl compounds is poorly characterized in the ambient atmosphere. In this study, we investigate their partitioning by simultaneously measuring six carbonyl compounds (formaldehyde, acetaldehyde, acetone, propionaldehyde, glyoxal, and methylglyoxal) in gas and particle phase at an urban site in Beijing. The field-derived partitioning coefficients (Kpf) are in the range of 10−5−10−3 m3 µg−1, and corresponding effective Henry’s law coefficients (KHf) should be 107–109 M atm−1. The Pankow’s absorptive partitioning theory and the Henry’s law both significantly underestimate concentrations of particle-phase carbonyl compounds (105–106 times and >103 times, respectively). The observed “salting in” effects only partially explain the enhanced partitioning to particles, approximately one order of magnitude. The measured Kpf values are higher at low relative humidity and the overall effective vapor pressure of these carbonyl species are lower than their hydrates, indicating that carbonyl oligomers potentially formed in highly concentrated particle phase. The reaction kinetics of oligomer formation should be included if applying the Henry’s law to low-to-moderate RH and the high partitioning coefficients observed need further field and laboratory studies. These findings provide deeper insights into the formation of carbonyl secondary organic aerosols in the ambient atmosphere.